Cost-Effectiveness of Treatment Options for Neuropathic Pain: a Systematic Review - Ruiz-Negrón, Natalia; Menon, Jyothi; King, Jordan B.; Ma, Junjie; Bellows, Brandon K. (PharmacoEconomics, 2019)
Background Neuropathic pain significantly reduces an individual’s quality of life and places a significant economic burden on society. As such, many cost-effectiveness analyses (CEAs) have been published for treatments available for neuropathic pain. Objectives The primary objective of this systematic review was to provide a detailed summary of the estimates of cost-effectiveness from published CEAs comparing available treatments for neuropathic pain. The secondary objectives were to identify the key drivers of cost-effectiveness and to assess the quality of published CEAs in neuropathic pain. Methods We searched Embase, MEDLINE, Cochrane CENTRAL and seven other databases to identify CEAs reporting the costs, health benefits (e.g., quality-adjusted life-years or disability-adjusted life-years) and summary statistics, such as incremental cost-effectiveness ratios, of treatments for neuropathic pain. We excluded studies reporting diseases other than neuropathic pain, those for which the full text was not available (e.g., conference abstracts), studies not written in English or not published in peer-reviewed journals, and narrative reviews, editorials and opinion papers. Titles and abstract reviews, full-text reviews, and data extraction were all performed by two independent reviewers, with disagreement resolved by a third reviewer. Mean costs, health benefits, and summary statistics were reported and qualitatively compared across studies, stratified by time horizon. Drivers of cost-effectiveness were assessed using reported one-way sensitivity analyses. The quality of all included studies was evaluated using the Tufts CEA Registry Quality Score and study reporting using the CHEERS (Consolidated Health Economic Evaluation Reporting Standards) checklist. Results A total of 22 studies were identified and included in this systematic review. Included studies were heterogeneous in the treatments compared, methodology and design, perspectives, and time horizons considered, making cross-study comparisons difficult. No single treatment was consistently the most cost-effective across all studies, but tricyclic antidepressants were the preferred treatment at a willingness-to-pay threshold of $US50,000 per quality-adjusted life-year in several studies with a short time horizon and a US payer perspective. Among the 14 studies reporting one-way sensitivity analyses, drivers of cost-effectiveness included utility values for health states and the likelihood of pain relief with treatment. The quality of the identified CEAs was moderate to high, and overall reporting largely met CHEERS recommendations. Limitations To assess drivers of cost-effectiveness and quality, we only included studies with the full text available and thus excluded some CEAs that reported cost-effectiveness results. The heterogeneity of the included studies meant that the study results could not be synthesized and comparison across studies was limited. Conclusions Though many pulished studies have evaluated the cost-effectiveness of treatments for neuropathic pain, significant heterogeneity between CEAs prevented synthesis of the results. Standardized methodology and improved reporting would allow for more reliable comparisons across studies.